A Bibliometric Analysis of Microneedle-Mediated Drug Delivery: Trends, Hotspots, and Future Directions - Xiang W; Jiang X; Guo L (Drug Design, Development and Therapy)
Weiyi Xiang,1,2 Xian Jiang,1,2,* Linghong Guo1,2,* 1Department of Dermatology, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Laboratory of Dermatology, Clinical Institute of Inflammation and Immunology, Frontiers Science Center for Dis-Ease-Related Molecular Network, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Linghong Guo, Department of Dermatology, West China Hospital, Sichuan University, No. 37, Guoxue Alley, Chengdu, Sichuan, People’s Republic of China, Tel +86 18380131660, Email linhom.guo@foxmail.comPurpose: Microneedles can physically penetrate the stratum corneum, creating micropores on the skin, and allowing for drug delivery through direct diffusion, injection, or other methods. As a novel drug delivery method, it possesses significant application potential. This study uses bibliometric analysis to explore the research hotspots and development trends of microneedle-mediated drug delivery.Methods: Relevant research articles on microneedle-mediated drug delivery published between 1998 and 2024 in the Web of Science Core Collection (WoSCC) database were retrieved. Data analysis and visualization were performed using VOSviewer, CiteSpace, Scimago Graphica, and Pajek, enabling the prediction of research trends in microneedle-mediated drug delivery.Results: In general, research on microneedle-mediated drug delivery has shown a continuous increase. China and the United States are the leading countries in this field of study. Notably, Ryan F. Donnelly (n=224) is the most prominent contributor to this field. The current core research directions include: disease treatment, enhancement of transdermal absorption performance of microneedles, vaccine delivery, and new materials and technologies for microneedle manufacturing.Conclusion: Microneedle-mediated drug delivery, as a novel technology and method, holds significant research value and application potential. However, further strengthening of international collaboration and the clinical translation of research findings are needed.Keywords: percutaneous drug delivery, research trends, vaccine delivery, materials science